Impact of short-term temperature challenges on the larvicidal activities of the entomopathogenic watermold Leptolegnia chapmanii against Aedes aegypti, and development on infected dead larvae - Muniz, Elen R. (2018)
The oomycete Leptolegnia chapmanii is among the most promising entomopathogens for biological control of Aedes aegypti. This mosquito vector breeds in small water collections, where this aquatic watermold pathogen can face short-term scenarios of challenging high or low temperatures during changing ambient conditions, but it is yet not well understood how extreme temperatures might affect the virulence and recycling capacities of this pathogen. We tested the effect of short-term exposure of encysted L. chapmanii zoospores (cysts) on A. aegypti larvae killed after infection by this pathogen to stressful low or high temperatures on virulence and production of cysts and oogonia, respectively. Cysts were exposed to temperature regimes between −12 °C and 40 °C for 4, 6 or 8 h, and then their infectivity was tested against third instar larvae (L3) at 25 °C; in addition, production of cysts and oogonia on L3 killed by infection exposed to the same temperature regimes as well as their larvicidal activity were monitored. Virulence of cysts to larvae and the degree of zoosporogenesis on dead larvae under laboratory conditions were highest at 25 °C but were hampered or even blocked after 4 up to 8 h exposure of cysts or dead larvae at both the highest (35 °C and 40 °C) and the lowest (−12 °C) temperatures followed by subsequent incubation at 25 °C. The virulence of cysts was less affected by accelerated than by slow thawing from the frozen state. The production of oogonia on dead larvae was stimulated by short-term exposure to freezing temperatures (−12 °C and 0 °C) or cool temperatures (5 °C and 10 °C) but was not detected at higher temperatures (25 °C–40 °C). These findings emphasize the susceptibility of L. chapmanii to short-term temperature stresses and underscore its interest as an agent for biocontrol of mosquitoes in the tropics and subtropics, especially A. aegypti, that breed preferentially in small volumes of water that are generally protected from direct sunlight.